2013
DOI: 10.1007/s00299-013-1469-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AtWRKY28 and AtWRKY75 in Arabidopsis enhances resistance to oxalic acid and Sclerotinia sclerotiorum

Abstract: Based on Arabidopsis microarray, we found 8 WRKY genes were up-regulated with Oxalic acid (OA) challenge, AtWRKY28 and AtWRKY75 overexpression lines showed enhanced resistance to OA and Sclerotinia sclerotiorum. The WRKY transcription factors are involved in various plant physiological processes and most remarkably in coping with diverse biotic and abiotic stresses. Oxalic acid (OA) is an important pathogenicity-determinant of necrotrophic phytopathogenic fungi, such as Sclerotina sclerotiorum (S. sclerotiorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 46 publications
3
91
0
Order By: Relevance
“…Since woundactivation of VSP2 was strongly diminished in wrky75-25 and maintained after egg extract treatment in 35S: WRKY75, our results are consistent with a positive role of WRKY75 in the control of the JA-regulated genes independently of MYC2. WRKY75 was previously shown to play a role in plant defense against biotrophs and necrotrophs (Encinas- Villarejo et al, 2009;Windram et al, 2012;Chen et al, 2013). Noteworthy, WRKY75 overexpression was accompanied by elevated expression of JA-responsive genes, including PDF1.2, VSP1, and LOX2, and enhanced resistance against the necrotroph Sclerotinia sclerotiorum .…”
Section: Discussionmentioning
confidence: 97%
“…Since woundactivation of VSP2 was strongly diminished in wrky75-25 and maintained after egg extract treatment in 35S: WRKY75, our results are consistent with a positive role of WRKY75 in the control of the JA-regulated genes independently of MYC2. WRKY75 was previously shown to play a role in plant defense against biotrophs and necrotrophs (Encinas- Villarejo et al, 2009;Windram et al, 2012;Chen et al, 2013). Noteworthy, WRKY75 overexpression was accompanied by elevated expression of JA-responsive genes, including PDF1.2, VSP1, and LOX2, and enhanced resistance against the necrotroph Sclerotinia sclerotiorum .…”
Section: Discussionmentioning
confidence: 97%
“…43 Furthermore, overexpression of WRKY28 , in Arabidopsis led to increased resistance to the necrotrophic pathogen, Sclerotinia sclerotiorum . 44 Thus, increased expression of these genes in resistant ‘Vlaspik’ 16 dpp peels could function as a developmentally regulated mechanism in ARR to P. capsici .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the HvWRKY12 gene was not upregulated during senescence induced by carbohydrate accumulation as a result of steam girdling (Parrot et al , 2007). AtWRKY75 , its orthologous gene in Arabidopsis (Mangelsen et al , 2008), was reported to be upregulated during senescence (Guo et al , 2004b) and in response to pathogens (Chen et al , 2013). OsWRKY72 , its orthologous gene in rice, could be induced by treatment with ABA (Xie et al , 2005).…”
Section: Discussionmentioning
confidence: 99%